CHARACTERISTICS OF SPENT LAYING HENS MEAT MARINATED WITH BINAHONG LEAF EXTRACT - I P. W., Sandhi; Okarini, I. A.; Wijana, I W. (Jurnal Peternakan Tropika, 2021)
This study aims to determine the effect of consentration and marination time in binahong leaf extract on the physical and subjective quality of spent laying hens. This study was conducted at the Laboratory of Animal Products Technology and Microbiology, Faculty of Animal Husbandry, Udayana University, Sudirman Campus, Denpasar for one month. The design used was a factorial completely randomized design (CRD) with two factors, namely the concentration factors of binahong leaf extract (K0: 0%, K1: 1.25%, and K2: 2.5%) and the factor for duration of marinated ?in binahong leaf extract (P0: 0 hour, P1: 1 hours, P3: 3 hours, and P5: 5 hours). Each treatment combination was repeated 3 times. The variables observed were cooking losses, pH, and organoleptic tests (texture of raw and cooked meat, aroma of raw and cooked meat, and taste of cooked meat). The results showed that the treatment factor for concentration had no significant effect on the physical characteristics and subjective value of meat (P>0.05). The treatment factor for the duration of marinated had no effect on the organoleptic test (P>0.05), but the duration of marinated was able to increase cooking losses and was able to decrease the pH value (P<0.05). The interaction between the two factors showed that K2P5 treatment could reduce cooking losses compared to K1P53 treatment (P<0.05), but had no effect on pH and organoleptic tests (P>0.05). Based on the results of the study, it can be concluded that the concentration of 2.5% and the duration of marinated of 5 hours in binahong leaf extract (K2P5) increased the organoleptic quality of the spent laying hens and can improve the results of the physical characteristic of the meat.   Keywords:       binahong, physical quality, spent, organoleptic